The eﬀect of low-level laser therapy on peripheral nerve lesions: a systematic review - Rashad, Usama M.; Badawy, Mohammad Sadik; Fahmy, Asmaa Abdelkader; El Fakharany, Mahmoud S.; Elsherif, Abdelaziz Abdelaziz (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Peripheral nerve lesions (PNLs) are highly prevalent among humans and lead to severe and long-term physiological and functional disabilities. This systematic review assessed low-level laser therapy (LLLT) on PNL patients as a safe conventional intervention.Methods. PubMed, Google Scholar, the Physiotherapy Evidence Database (PEDro), Scopus, Egyptian Knowledge Bank, and Cochrane Central databases were searched for relevant articles published between 2007 and 2024 (last search update: July 1st, 2024). Two independent authors reviewed the data extracted from the included articles to evaluate variability, while the PEDro scale assessed methodological quality. Variables and outcomes assessed included pain intensity [visual analogue scale (VAS)], sensory nerve conduction velocity (SNCV), and compound motor action potential [assessed by electromyography (EMG)]. For the meta-analysis, a random-eﬀects model was applied using mean diﬀerence (MD) with 95 % conﬁdence intervals (CIs).Results. The initial search yielded 1539 articles, of which only eight were included in this review. The results of the included studies revealed evidence of positive eﬀects of laser therapy in PNL patients, with pain intensity (p = 0.02) treated more eﬀectively than SNCV (p = 0.01). However, no eﬀect on compound motor action potential was found (p = 0.56). The data analysis derived pooled MD values for pain intensity (Z = 2.38), SNCV (Z = 2.59), and compound action potential (Z = 0.58).Conclusions. The evidence supports that LLLT beneﬁts PNL patients by reducing pain intensity and improving sensory electro-physiological outcomes, but no improvements were found for motor electrophysiological outcomes.
Keywords: performance-based speed; physical training; hemiparesis; balance; walking